A Comparative Study for Removal of Perfluorooctanoic Acid Using Three Kinds of N-polymer Functionalized Calotropis Gigantea Fiber. Issue 6 (3rd June 2022) - Niu, Bihui; Yu, Min; Sun, Changduo; Wang, Luhan; Niu, Yanning; Huang, Huimin; Zheng, Yian
ABSTRACT: Using NaClO2 pretreated Calotropis gigantea fiber (CGF) as the bio-template, three N-polymer functionalized fibers were fabricated by in-situ growth of polydopamine (PDA), polyaniline (PAN) and poly( m -phenylenediamine) (PmPD) along the fiber. The resulting adsorbents were applied to remove perfluorooctanoic acid (PFOA) from water. The adsorption process reached equilibrium within 3 h, and the maximum adsorption capacity was 207.3–232.8 mg/g. Electrostatic attraction, hydrogen bond and hydrophobic interaction participated in the adsorption process. Three adsorbents could be well regenerated, and the recovered adsorbents maintained higher adsorption percentage (≥80%) after five adsorption-desorption cycles. Among three adsorbents, PAN-CGF displayed remarkable adsorption performance on perfluorochemicals removal.